2019
DOI: 10.1201/9781351062268
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Modeling Using R

Abstract: This book is from the "Statistics in the Social and Behavioral Sciences" series of Chapman and Hall/CRC, which has quite a broad scope. The book's preface states its goals as follows: "The goal of this book is to provide [...] a comprehensive resource for the conduct of multilevel modeling using the R software package." "Our goal is to provide you with a guidebook that will serve as the launching point for your own investigations into multilevel modeling". The content suggests that the book is written for R no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(61 citation statements)
references
References 6 publications
0
56
0
5
Order By: Relevance
“…To account for the nonindependence of observations (daily assessments nested within individuals), we estimated the effect of trait self-control on daily loneliness using multilevel regression. The models included a random intercept at the level of participants; to account for longitudinal data structure, we additionally specified an error structure that allowed for correlations between adjacent time points for the same participant (Finch et al, 2019). Model 1 (see Table 3) showed that individuals with lower trait self-control experienced more loneliness within the observation period (7 days; b = −0.75, p < .001, 95% CI = [−0.92; −0.58]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for the nonindependence of observations (daily assessments nested within individuals), we estimated the effect of trait self-control on daily loneliness using multilevel regression. The models included a random intercept at the level of participants; to account for longitudinal data structure, we additionally specified an error structure that allowed for correlations between adjacent time points for the same participant (Finch et al, 2019). Model 1 (see Table 3) showed that individuals with lower trait self-control experienced more loneliness within the observation period (7 days; b = −0.75, p < .001, 95% CI = [−0.92; −0.58]).…”
Section: Resultsmentioning
confidence: 99%
“…We used multilevel regression, with assessments nested within participants. The analyses included a random effect of participants; to account for longitudinal data structure, we additionally specified an error structure that allowed for correlations between adjacent time points for the same participant (Finch et al, 2019). We centered all continuous predictors within-persons (Enders & Tofighi, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Fixed effects were tested at the level of participants (i.e., Level 2). This statistical approach accounts for dependency within participants and introduces less bias related to missing data compared to traditional statistical analyses, such as repeated-measures analysis of variance (Finch, Bolin, & Kelley, 2014; Raudenbush & Bryk, 2002). All analyses were conducted using the R statistical programming language, version 3.4.0 (R Core Team, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In short, it is not certain that multisite experiments are the way out of the powerlessness problem. Perhaps design details, like block randomization (Gill & Weisburd, 2013), or alternative analytics like mixed models (Browne, Lahi, & Parker, 2009;Finch, Bolin, & Kelley, 2019), might sufficiently enhance the statistical power of multicity studies focusing on micro-scaled predictive policing to make them minimally viable. But this, too, is an empirical question.…”
Section: Discussionmentioning
confidence: 99%